The Role of Trust in Cooperative Relationships Between Project-based Companies: Results of the Qualitative Study - Janusz Marek LICHTARSKI; Krzysztof ĆWIK (Communications of International Proceedings, 2025)
The role of trust in interfirm relationships is underestimated, especially in project-based companies that rely on temporary and dynamic forms of collaboration. This study addresses this important topic by examining how trust influences the development of inter-organizational relationships in project-based settings. Employing a qualitative research design, the study combines a systematic literature review with a case study analysis. Eight project-based firms (24 dyads) were investigated through in-depth semi-structured interviews and documentary analysis. The findings reveal unique life-cycle patterns of interfirm relationships and the critical role of trust in their development. While companies actively seek trustworthy partners, they frequently initiate cooperation with unfamiliar organizations, often relying on formal mechanisms to compensate for the absence of initial trust. A high level of trust offers various benefits, including reduced transaction costs, improved knowledge exchange, and the potential for reactivating collaboration in future projects. Also, interpersonal trust emerged as a vital component of successful interfirm cooperation. Although the study is exploratory and limited in generalizability, it lays the groundwork for future research and provides a novel framework for understanding relationship dynamics in project-based environments. This makes it a valuable contribution to both theory and managerial practice.
Keywords: organisational trust; interfirm relationships; project-based company